2020
DOI: 10.14710/ijfst.16.3.171-178
|View full text |Cite
|
Sign up to set email alerts
|

Air-Sea Flux of Co2 in the Waters of Karimunjawa Island, Indonesia

Abstract: The purpose of this study was to determine the distribution of CO2 flux in Karimunjawa in the east monsoon.  The variables in this study were temperature; pH; salinity; DO; CO2 atm was measured using a CO2 meter; chlorophyll-a, phosphate, silicate were measured spectrophotometric method. Total Alkalinity / TA was measured using the titration method with the principle of changing pH; DIC (Dissolved Inorganic Carbon) was measured using CO2sys software. The partial pressure of seawater carbon dioxide calculated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…This huge amount of carbon stored in the mangrove above ground biomass indicates the role of mangrove ecosystem in the Karimunjawa-Kemujan Islands in absorbing the atmospheric CO 2 which is naturally released by the Java Sea. As an illustration, Latifah et al [12] stated that the CO 2 release by the seas surrounding Karimunjawa Islands ranges from 8.549 to 13.272 mmol/m 2 /day with a mean value of about 10 mmol/m 2 /day. This mean value is equal to 3.2 g C/m 2 /day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This huge amount of carbon stored in the mangrove above ground biomass indicates the role of mangrove ecosystem in the Karimunjawa-Kemujan Islands in absorbing the atmospheric CO 2 which is naturally released by the Java Sea. As an illustration, Latifah et al [12] stated that the CO 2 release by the seas surrounding Karimunjawa Islands ranges from 8.549 to 13.272 mmol/m 2 /day with a mean value of about 10 mmol/m 2 /day. This mean value is equal to 3.2 g C/m 2 /day.…”
Section: Discussionmentioning
confidence: 99%
“…The releasing carbon to the atmosphere occurs at maximum during the first transition season (April-May). Focusing on the seas of the Karimunjawa Islands, which was left blank by Kartadikaria et al [10] and Wirasatriya et al [11], Latifah et al [12] also found that the seas of the Karimunjawa Island act as a carbon source by conducting in-situ CO 2 measurement. Thus, it is crucial to investigate the role of the mangrove ecosystems in the Karimunjawa Islands as a contra role of the Java Sea in releasing carbon for a future possibility of the calculating carbon budget in the region.…”
Section: Introductionmentioning
confidence: 99%
“…At high latitudes with cold waters, the solubility of CO2 is high which can increase the dissolution of gas into seawater causing CO2 absorption (sink CO2) to occur. This is supported by other studies which conclude that high-latitude seas/oceans with four seasons and relatively cold temperatures function as CO2 absorbers (Takahashi et al, 1997;Takahashi et al, 2002;Cai et al, 2006;Yasunaka et al, 2016;Arnone et al, 2017;Ito et al, 2018;Tian et al, 2020) while low latitudes seas function as a source of CO2 due to warm waters (Fitranti et al, 2013;Kartadikaria et al, 2015;Afdal, 2016;Yan et al, 2018;Latifah et al, 2020). Several studies in Indonesia, however, show that the sea can function as sinks of CO2 (Fachri et al, 2015;Latifah et al, 2019).…”
Section: Introductionmentioning
confidence: 61%
“…Water quality variables that affect CO2 Flux Previous studies (Takahashi et al, 1997;Takahashi et al, 2002;Cai et al, 2006;Takahashi et al, 2009;Otero et al, 2013;Yasunaka et al, 2016;Arnone et al, 2017;Ito et al, 2018;Tian et al, 2020) showed that in waters in middle and high latitudes with low temperatures, the oceans acted as CO2 sinks. While studies conducted at low latitudes with high (warm) temperatures (Fitranti et al, 2013;Kartadikaria et al, 2015;Afdal, 2016;Yan et al, 2018;Latifah et al, 2020) showed that the oceans served as a source of CO2. Warm surface water causes CO2 to be returned to the atmosphere by the oceans (outgassing of CO2).…”
Section: Fluxes Of Co2mentioning
confidence: 99%
“…The CO 2 system in waters is in the form of gas (CO 2 ), bicarbonic acid, bicarbonate ions and carbonate ions. The total amount of all forms of the CO 2 system is called the total CO 2 concentration [∑CO 2 ] and is often called dissolved inorganic carbon (DIC) (Latifah et al, 2020). The presence of inorganic carbon plays an important role in chemical reactions in waters.…”
Section: Introductionmentioning
confidence: 99%